Validity of Abdominal Ct Scan Scoring System in Distinguishing Benign and Malignant Ovarian Tumors - Kezia Sondang Mukti; Pande Putu Yuli Anandasari; I Gusti Agung Gede Mahendra; I Wayan Gede Artawan Eka Putra (Green Publisher Indonesia, 2025)
Ovarian tumors are one of the most commonly found gynecological malignancies, with significant differences in characteristics between benign and malignant tumors. An abdominal CT scan is often used to evaluate ovarian mass, but there is no standard scoring system to determine ovarian tumor malignancy based on imaging findings. This study aims to obtain the validity of the abdominal CT scan scoring system in distinguishing benign and malignant ovarian tumors. This study is an observational study with a diagnostic test by analyzing 70 cases of ovarian tumors that have been confirmed through histopathology at Ngoerah Hospital. The variables analyzed included socio-demographic characteristics such as menarche age and family history of malignancy (breast or ovarian malignancy), tumor size, location, tumor components, wall thickness, septa, papillary projection, contrast enhancement, as well as additional findings such as ascites and pelvic organ invasion. Statistical analysis was performed to assess the relationship between these variables and the malignancy status of ovarian tumors. Of the total 70 cases, 53 masses (75.7%) were malignant and 17 masses (24.3%) were benign. The analysis showed that parameters such as bilateral location, solid-cystic components, contrast enhancement, as well as the presence of ascites, thickening of the peritoneum, and invasion of the pelvic organs had a higher tendency to malignancy, although some variables did not show statistical significance. The scoring system developed showed that the cut-off score ≥4 had a sensitivity of 83.02% and specificity of 64.7%, positive predictive value of 88%, negative predictive value of 55%, with diagnostic accuracy of 78.57%.